(untitled) (Scientific journal of the Fergana State University, 2024)
These students’ mastery of professional knowledge and pedagogical innovations related to preparation and organization of project activities, their cognitive activities and professional independence, and their desire to master the culture of pedagogical activity, will enable them to acquire the competencies of effectively organizing the educational process.